Freshwater vertebrates monitoring in Maninjau Lake, West Sumatra, Indonesia using environmental DNA: - - DEWI IMELDA ROESMA; HON TJONG DJONG; MUHAMMAD NAZRI JANRA; DYTA RABBANI AIDIL (Society for Indonesian Biodiversity, 2021)
Abstract. Roesma DI, Tjong DH, Janra MN, Aidil DR. 2021. Freshwater vertebrates monitoring in Maninjau Lake, West Sumatra, Indonesia using environmental DNA. Biodiversitas 22: 2794-2802. Environmental DNA (eDNA) is one of the DNA sources without directly disturbing the organisms. The eDNA potentially an effective method with next-generation sequencing (NGS) that can read all DNA in parallel at one sequential run. Maninjau Lake in West Sumatra has experienced a decline the species richness, thus monitor biodiversity with the non-invasive method is needed. This study aimed to apply eDNA for monitoring freshwater vertebrates in Maninjau Lake. The eDNA was collected from water samples using the filter membrane to DNA isolation and sequencing with the NGS technique from Illumina. The eDNA method detected 150 vertebrate individuals and consists of 92 Actinopterygii fishes, three chondrichthyes fishes, 11 amphibians, seven reptiles, ten aves, and 27 mammals. Among all individuals were detected, only 11% known present in Maninjau Lake, while the others (89%) are native species to other countries. The fishes were detected living in Maninjau Lake by the eDNA method, i.e., Cyprinidae (Carassius auratus and Cyprinus carpio), Cichlidae (Oreochromis niloticus), and Poeciliidae (Gambusia affinis and Xiphophorus maculatus). Bias results in this study to be influenced by various factors i.e., possibility of contamination, poor DNA quality, the bias results during molecular processes, and not available the complete sequences databases to assigned into the correct taxa, especially fish species in Maninjau Lake. The eDNA method for monitoring biodiversity should consider the increase of sampling sites, replication samples, and the availability of sequences database in Genbank, NCBI